Data Generation with Variational Autoencoders and Generative Adversarial Networks - Daniil Devyatkin; Ivan Trenev (Engineering Proceedings, 2023)
The paper considers the problem of modelling the distribution of data with noise in the input data. In this paper, we consider encoders and decoders, which solve the problem of modelling data distribution. The improvement of variational autoencoders (VAEs) is discussed. Practical implementation is performed using the Python programming language and the Keras framework. Generative adversarial networks (GANs) and VAEs with noisy data are demonstrated.